Digitalization of traditional markets through tumbasin.id in facing industrial revolution 4.0: The Islamic business perspectives - Faizah, Fita Nurotul; Septiana, Vira (LPMP Imperium, 2024)
This research explores how Tumbasin.id contributes to the digitization of traditional markets amidst the Fourth Industrial Revolution, focusing on its role in market development from the perspective of Islamic business ethics. Using a descriptive qualitative method involving interviews, observation, and documentation, the study reveals that Tumbasin.id innovatively connects traditional market traders and buyers in Semarang City. The tagline